Cooperation of the Republic of Kazakhstan and the European Union in the environmental fi eld (International relations and international law Journal, 2016)
This article discusses the environmental problems in Central Asia, including Kazakhstan. Among the most pressing problems of the Central Asian region in the field of environment and natural resources are: conservation issues in the areas of large territorial-industrial complexes, the problems of the Aral Sea, the protection of water resources management, oil, radioactive and industrial waste, polluting the rivers and lakes of the region, environmental problems in agriculture, desertification, air pollution, etc. The European Union is actively cooperating with the Republic of Kazakhstan in the environmental field in the framework of Agreement on Partnership and Cooperation Agreement. The article also discusses the main projects of the European Union TACIS program for the protection and conservation of the environmental problems of the Republic of Kazakhstan.
Keywords: European Union; the Republic of Kazakhstan; Central Asia; environmental issues and the environment